2019
DOI: 10.1080/03007995.2019.1699516
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating patient-perceived control of atopic dermatitis: design, validation, and scoring of the Atopic Dermatitis Control Tool (ADCT)

Abstract: Objectives: The Atopic Dermatitis Control Tool (ADCT) was designed to evaluate patient-perceived AD control and facilitate patient-physician discussion on long-term disease control. Methods: The study was performed in adult patients with AD. Development of the ADCT followed US Food and Drug Administration (FDA) guidelines on patient-reported outcome measures (PROMs). Qualitative research, including targeted literature review, interviews with clinical experts, and combined concept elicitation/cognitive debriefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 39 publications
1
66
0
5
Order By: Relevance
“…To confirm known-groups validity, mean ADCT total scores were compared across adjacent subgroups of patients based on PGAD responses (Excellent, Very good, Good, Fair, Poor) and categories of DLQI responses: no effect on patient life (score range: 0-1), a small effect (2-5), a moderate effect (6-10), a very large effect (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), an extremely large effect (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [36] ( Table 1). Patients in a worse PGAD or DLQI band subgroup were expected to display poorer AD control (i.e., higher mean ADCT total scores, indicating more severe symptoms/greater impact) than patients in a better PGAD or DLQI band subgroup.…”
Section: Known-groups Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm known-groups validity, mean ADCT total scores were compared across adjacent subgroups of patients based on PGAD responses (Excellent, Very good, Good, Fair, Poor) and categories of DLQI responses: no effect on patient life (score range: 0-1), a small effect (2-5), a moderate effect (6-10), a very large effect (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), an extremely large effect (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [36] ( Table 1). Patients in a worse PGAD or DLQI band subgroup were expected to display poorer AD control (i.e., higher mean ADCT total scores, indicating more severe symptoms/greater impact) than patients in a better PGAD or DLQI band subgroup.…”
Section: Known-groups Validitymentioning
confidence: 99%
“…An initial evaluation of the psychometric properties of the instrument in the United States has indicated that the ADCT is valid and reliable for assessing patient-perceived AD control in adults [29]. In addition, a score of ≥7 points was derived as the threshold to identify patients "not in control", based on optimal sensitivity/specificity values [29]. The ADCT© is protected by copyright with all rights reserved to Sanofi, and its development partners.…”
mentioning
confidence: 99%
“…Each of the six ADCT items has a score range from 0 (no problem) to 4 (worst), rating the severity of each concept; the total score ranges from 0 to 24, which is the summation of the responses to all the items. An initial evaluation of the psychometric properties of the instrument in the United States has indicated that the ADCT is valid and reliable for assessing patient-perceived AD control in adults [29]. In addition, a score of ≥7 points was derived as the threshold to identify patients "not in control", based on optimal sensitivity/specificity values [29].…”
Section: Introductionmentioning
confidence: 99%
“…The Atopic Dermatitis Control Tool (ADCT©) is a new PROM designed to assess patient-perceived disease control, meeting this current measurement gap in the management of patients with AD (ADCT v1; https://patient-questionnaires.sanofi.com/questionnaires/adct-atopic-dermatitis-controlcommunication-tool) [29]. It is envisaged that the tool will also foster patient-clinician communication regarding disease control.…”
Section: Introductionmentioning
confidence: 99%
“…An initial evaluation of the psychometric properties of the instrument in the United States has indicated that the ADCT is valid and reliable for assessing patient-perceived AD control in adults. In addition, a score of ≥7 points was derived as the threshold to identify patients "not in control", based on optimal sensitivity/specificity values [29].…”
Section: Introductionmentioning
confidence: 99%